The Compatibility of Area Functions Map with Actual Site Conditions in Konawe Selatan District - La Ode Nursalam; Agus Sugiarto; Putri Tipa Anasi; Ahmad Tarmizi Abd Karim; Fahrudi Ahwan Ikhsan; Andri Estining Sejati (Department of Geography Education, University of Jember, 2022)
The Konawe Selatan District region is characterized by Karst hills, various soil types, and steep slopes. Functional classification considers the physical and non-physical characteristics of the location to determine its many uses. The map developed by the Regulation of the Agriculture Minister of Indonesia should be checked with the actual condition for the validation process before presenting to the society and Local government. Therefore, this research aimed to determine the compatibility of the area function map result with the actual conditions in Konawe Selatan District, Southeast Sulawesi, Indonesia. The research is a regional survey, collecting data from interviews and observations, and the data were analyzed descriptively and quantitatively with percentages. The results show that the compatibility of the Konawe Selatan District area function map is 89.61%, functioning as a guideline in the land use plan. Furthermore, the map could guide potential land-use planning functions such as protected forests, limited production forests, rice fields, and settlements. In conclusion, the map is appropriate for disseminating information and material for land use policies in Konawe Selatan District to stakeholders. Keywords : actual condition; area function; compatibility; map Copyright (c) 2022 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License